TRENDS IN IMPLEMENTATION OF TECHNOLOGY USE IN MATHEMATICS EDUCATION ON SCOPUS DATABASE: BIBLIOMETRIC ANALYSIS - Bin Zabidi, Muhammad Aqil Naim; Bakti, Anugrah Arya; Sultan, Jumriani; Ayuni, Rizki Tika; Arriza, Lovieanta (Mathematics Research and Education Journal, 2024)
This study aims to analyze the trend of technology implementation in mathematics education in the Scopus Database using bibliometric analysis. Using predetermined keywords, researchers analyzed 251 documents using RStudio and Vosviewer. From the analysis conducted, it can be concluded that this study shows an interesting growth pattern in research on the use of technology in mathematics education over the period 1977 to 2024. This pattern changed significantly in the last 15 years, from 2009 to 2024, which is equivalent to four times the previous figure, or 66.13% of the total. The University of Pretoria dominated with the highest number of publications, at 14 articles. The source "Educational Studies in Mathematics" stands out as the best source with the highest h-index, at 5. Marien Alet Graham stands out as the author with the highest h-index, at 3. The paper Drijvers et al. (2010) stands out with the highest number of citations, at 168. There were 46 keywords divided into 6 groups, with the keywords Whatsapp, Geogebra, Science Technologies, and Collaborative Learning potentially being interesting and innovative research subjects related to Technology in Mathematics Education.